1978
DOI: 10.1007/bf01477249
|View full text |Cite
|
Sign up to set email alerts
|

Der Zusammenhang zwischen Prognose und Kieler Klassifikation der malignen Non-Hodgkin-Lymphome

Abstract: The clinical course of 201 patients with malignant non-Hodgkin-lymphomas was analysed according to the Kiel classification. The five-year survival rate of 133 patients with lymphomas of low grade malignancy was 63% in comparison to 23% out of 68 patients with lymphomas of high grade malignancy. Radio- and chemotherapy were used in a different way. Patients with centrocytic-centroblastic lymphomas had the best porgnosis, which was not influenced by the stage of the disease. The poorest prognosis was observered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
3

Year Published

1981
1981
1995
1995

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 5 publications
1
2
0
3
Order By: Relevance
“…In continental Europe, use of the Rappaport classification remained scanty, and in the early seventies the Kiel classification, differentiating NHL by modern histo-and cytopathology and immunology, has been widely accepted by pathologists so that detailed studies of its clinical and prognostic implications became necessary. From 1973 to 1975, a retrospective investigation on 405 patients performed by the Kiel Lymphoma Study Group (KLSG) comprising 21 hospitals in West Germany and Austria (Brittinger et al, 1976Stacher et al, 1976;Bremer et al, 1977), and data published by other groups (Diihmke, 1976;Musshoff et al, 1976;Diihmke and Quack, 1977;Delbriick et al, 1978;Meuge et al, 1978) showed that the subdivision by the Kiel classification of NHL into two major histopathological groups (NHL of low-grade and high-grade malignancy) as well as into several lymphoma entities subsumed under these headings has prognostic relevance. Since, however, several questions such as the prognostic relevance of histopathological subclassifications of certain lymphoma entities or the initial stage of disease could not be answered by these investigations, in 1975 the Kiel Lymphoma Study Group initiated a prospective multicenter observation study.…”
Section: Introductionmentioning
confidence: 99%
“…In continental Europe, use of the Rappaport classification remained scanty, and in the early seventies the Kiel classification, differentiating NHL by modern histo-and cytopathology and immunology, has been widely accepted by pathologists so that detailed studies of its clinical and prognostic implications became necessary. From 1973 to 1975, a retrospective investigation on 405 patients performed by the Kiel Lymphoma Study Group (KLSG) comprising 21 hospitals in West Germany and Austria (Brittinger et al, 1976Stacher et al, 1976;Bremer et al, 1977), and data published by other groups (Diihmke, 1976;Musshoff et al, 1976;Diihmke and Quack, 1977;Delbriick et al, 1978;Meuge et al, 1978) showed that the subdivision by the Kiel classification of NHL into two major histopathological groups (NHL of low-grade and high-grade malignancy) as well as into several lymphoma entities subsumed under these headings has prognostic relevance. Since, however, several questions such as the prognostic relevance of histopathological subclassifications of certain lymphoma entities or the initial stage of disease could not be answered by these investigations, in 1975 the Kiel Lymphoma Study Group initiated a prospective multicenter observation study.…”
Section: Introductionmentioning
confidence: 99%
“…Bemerkenswert Prognostisch gehört das Zentrozytom zu den niedrigmalignen Lym phomen (Tab. I), die eine signifikant günstigere Lebenserwartung haben als die hochmalignen [Bettini und Chelazzi, 1979;Bremer, 1977;Brittinger et al, 1976Brittinger et al, , 1978Delbrück et al, 1978;Diihmke, 1976;Mandardet al, 1977], Doch innerhalb der Gruppe mit niedriger Malignität kommt den Zentrozytomen möglicherweise eine Sonderstellung zu: Sie haben hier die schlechteste Pro gnose. Die mittlere Lebenserwartung beträgt 4 Jahre.…”
Section: Diskussionunclassified
“…Unsere Patientin kann dafür als Bei spiel dienen. Ansonsten sind die Zentrozytome im allgemeinen dadurch gekennzeichnet, dass sie ganz überwiegend zum Zeitpunkt der Diagnosestel lung generalisiert sind [Brittinger et al, 1976;Delbrück et al, 1978;Dühmke, 1976;König et al, 1979]. Aus diesem Grund wird das Zentrozytom auch als nichtleukämisches Gegenstück zur chronischen lymphatischen Leukämie be zeichnet [Becker, 1978].…”
Section: Diskussionunclassified
See 1 more Smart Citation
“…Several attempts have been made at classifying the heteroge nous group of non-Hodgkin lymphomas (NHL) [1], In Europe the Kiel classification has been widely used and has confirmed its relevance in several retrospective studies and one prospec tive trial [2][3][4][5][6][7]. New entities, e.g.…”
Section: Introductionmentioning
confidence: 99%